Identifikasi Alat Permainan Edukatif (APE) Dalam Mengembangkan Sains Sederhana Pada Anak Usia Dini Di Kecamatan Pringgabaya Kabupaten Lombok Timur - Nisa Zuliyana Afriani; Gunawan Gunawan; Baik Nilawati Astini; Ni Luh Putu Nina Sriwarthini (Indonesian Publication Center, 2023)
Educational Game Tools are all kinds of tools or objects used to play by early childhood that can stimulate aspects of development in children. The purpose of this study was to find out the APE of science used by teachers in developing simple science in early childhood in Pringgabaya Sub-district, East Lombok Regency. This type of research is survey research. The sample used in this research is 8 Kindergartens in Pringgabaya Sub-District with 23 respondents. Data collection methods used in this research are questionnaires, interviews, and documentation. As for the research results obtained, indoor APE which is often used by teachers in develoving simple science in early childhood in 8 Kindergartens of Pringgabaya Sub- District is 91,7% color mixing, and 69,9% inflatable balloon. While outdoor APE that is often used by teachers in develoving simple science in early childhood in Pringgabaya Sub-District is APE floating object, hovering, sinking 82,6%.